Maximizing Performance and Scalability with IBM WebSphere - Neat, Adam G. (Apress, 2012)
Over the past three years, IBM has proven WebSphere's power by molding it into a powerful, scalable, and robust Java 2 Enterprise Edition (J2EE) application server platform. Each major release since 3.5 has included impressive redundancy, scalability, and performance features that continue to put IBM WebSphere at the forefront of high-end J2EE computing.